2014
DOI: 10.1007/s00455-014-9545-6
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the Tongue-Hold Maneuver Using High-Resolution Manometry and Electromyography

Abstract: The tongue-hold maneuver is a widely used clinical technique designed to increase posterior pharyngeal wall movement in individuals with dysphagia. It is hypothesized that the tongue-hold maneuver results in increased contraction of the superior pharyngeal constrictor. However, an electromyographic study of the pharynx and tongue during the tongue-hold is still needed to understand whether and how swallow muscle activity and pressure may change with this maneuver. We tested eight healthy young participants usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 27 publications
4
54
3
Order By: Relevance
“…Pharyngeal HRM is limited by a seldom-reported measurement error in the ManoScan™ system, used widely in research [52,73,81,82,88,92,93,94,95]. A pressure drift has been found to refute the manufacturer's report that pressure uniformity remains within 2 mm Hg for 4 h or less of recording [93,96].…”
Section: Pharyngeal Manometrymentioning
confidence: 82%
See 2 more Smart Citations
“…Pharyngeal HRM is limited by a seldom-reported measurement error in the ManoScan™ system, used widely in research [52,73,81,82,88,92,93,94,95]. A pressure drift has been found to refute the manufacturer's report that pressure uniformity remains within 2 mm Hg for 4 h or less of recording [93,96].…”
Section: Pharyngeal Manometrymentioning
confidence: 82%
“…Research applications of HRM rely heavily on software such as MATLAB to analyse pharyngeal swallowing with custom algorithms outside of commercial HRM devices [78,79,80,81,82,83,91], and reliability of pharyngeal HRM is limited to one study investigating a custom MATLAB programme. The reliability of a custom-designed software programme was evaluated after provision of a 20-min training session to 20 raters with varying experience (e.g., expert and novice speech-language pathologists) [91].…”
Section: Pharyngeal Manometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The disuse of swallowing mechanism can reduce its cortical representation and corresponds to a threat to functional recovery at long term (26) . Studies (1,8) already describe that exercises in specific muscle groups, which view at swallowing, can have a significant contribution for the function rehabilitation. The significant reduction of clinic signs presence after performing the exercises reflects the functional improvement at feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Besides using adaptations at the moment of oral intake, it has been suggested a variety of exercise protocols to improve the swallowing capacity aiming at larger range of movement (3) , increase at the swallowing effort (4)(5)(6) and sensorial system impulse (7) . Among them are tongue-hold (8,9) , Shaker exercise (10) , counter-resistance exercise with head lowered (11) , tongue exercises (12) , Iowa Oral Performance Instrument -IOPI (13) , etc. Some studies (14)(15)(16) have shown a motor reorganization map as a feedback for therapeutic stimulation.…”
Section: Introductionmentioning
confidence: 99%